Light express. Issue 28 (December 2021) - Forlani, Giada; Di Ventura, Barbara
Abstract: Each of us is a unique individual despite carrying almost the same genetic information as anyone else. Zooming in into our body, we find the same pattern: all cells share the same genome, and yet they look and behave differently. The process of gene expression is the reason behind this fascinating phenomenon whereby the same genome is translated in different sets of molecules being present in the cell at any given time. The ability to precisely control this process endows researchers with great power, not only for basic science purposes but also for biotechnological and biomedical applications. In this review, we will discuss the current arsenal of tools that consent to control gene expression using light as the external trigger. These tools are, in most cases, preferable to those based on chemical triggers owing to the many favorable properties of light, foremost its spatial confineability and easy removal. Highlights: Gene expression dictates cell behavior. Controlling gene expression empowers researchers. Light is a perfect external trigger. Light-inducible gene expression systems abund.